2021
DOI: 10.1016/j.toxrep.2021.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity evaluation of Eleutherine plicata Herb. extracts and possible cell death mechanism

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…These results suggest the cytotoxicity of EEEp and FDMEp are related to the synergism between eleutherin and isoeleutherin compounds. When administered together they are more active, which may increase toxicity ( Vale et al, 2020 ; Gomes et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest the cytotoxicity of EEEp and FDMEp are related to the synergism between eleutherin and isoeleutherin compounds. When administered together they are more active, which may increase toxicity ( Vale et al, 2020 ; Gomes et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, using peritoneal macrophages from BALB/c mice, the cytotoxic activity of EEEp, its fractions (FDEp, FAEp and FMEp) and isoeleutherin were evaluated, with no cytotoxicity being observed. Gomes et al (2021), evaluated the cytotoxicity of EEEp, FDMEp and isoeleutherin from E. plicata in human hepatoma cells (HepG2), after exposure for 24 h, and observed that fractionation reduced cytotoxicity, with isoeleutherin being the least toxic sample. These results suggest the cytotoxicity of EEEp and FDMEp are related to the synergism between eleutherin and isoeleutherin compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In the subacute toxicity assay, EEEp and FDMEp also did not cause clinical, hematological, or biochemical changes. Moreover, isoeleutherine, eleutherine, and eleutherol ( Figure 1 ) bound similarly to caspase-8 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Urb.) has antibacterial potential (Padhi dan Panda, 2015;Munaeni et al, 2019;Novaryatiin et al, 2019) and provide natural antioxidant properties (Haerani et al, 2019;Shi et al, 2019;Munaeni et al, 2020a;Gomes et al, 2021). Bioactive compounds of Dayak onion contain naphthalene, naphthoquinone, anthraquinone (Insanu et al, 2014), flavonoid, saponin, tannin, steroid, dan triterpenoid (Munaeni et al, 2017).…”
Section: Introductionmentioning
confidence: 99%